Re-Imagining the Teaching of European History : Promoting Civic Education and Historical Consciousness. - Gómez Carrasco, Cosme Jesús. (Taylor & Francis Group, 2022)
This book explores the challenges of teaching European history in the 21st century and provides research-informed approaches to history teaching that combine civic education, historical consciousness and the teaching of controversial social issues.